Evaluation of research and national scientific journals. - Laborde, Javier (Instituto de Ecología, A.C., 2009)
Scientific papers published in Mexican and Latin American journals are usually assigned very low (or even null) value in the research evaluation systems that are currently prevalent in this region. Consequently, our scientists are publishing their most relevant research elsewhere, mainly in journals that are indexed in ISI’s Citation Index (CI) and have a high Impact Factor (IF) because these journals are the most highly valued by our evaluators. Latin American journals literally are being deprived of the best contributions from the region, making it even more difficult to acquire the international visibility needed for our journals to become more attractive to our researchers and evaluators. If this cycle continues, our journals will be condemned to a secondary role in the advancement of science and may even disappear. Several scientists have exposed the main problems and limitations of ISI’s CI and the IF as indicators of ‘good science’ and I review these here. I then briefly describe recently developed alternatives that should at least complement these indicators or possibly replace them in the evaluation of research. Finally, I reflect on current practices of research evaluation and propose some measures to break the vicious cycle in which our journals are trapped. My main objective is to contribute to the debate on the indicators employed in our evaluation systems and to stimulate the discussion of the far reaching consequences that the use of these indicators is having on the development of science in Latin America and on the future of our journals.